Activity of Alginate-Gelatin Hydrogels Containing Metal-Organic Frameworks Against Escherichia coli and Staphylococcus aureus for Wound Dressing Application - Mulyati, Tri Ana; Ekowati, Juni; Sariwati, Atmira; Agustina, Lia; Wardani, Siska; Erawati, Erawati; Pujiono, Fery (Institute of Topical Disease Universitas Airlangga, 2025)
Bacterial infections, such as S. aureus and E. coli, remain a global health issue, particularly concerning bacterial resistance, which often leads to serious complications. One approach to address this problem is the development of Metal Organic Frameworks (MOFs), known for their high conductivity and antibacterial activity. Zn-based MOFs are known to possess strong antibacterial activity because Zn²⁺ ions can damage bacterial cell membranes, disrupt enzymatic processes, and induce oxidative stress. In comparison, Zr-based MOFs are well known for their excellent chemical stability and biocompatibility. In this study, hydrogels containing three types of MOFs-Zn-BDC, Zn-Fer, and Zr-BDC were developed. This research aims to synthesize and characterize alginate-gelatin hydrogels containing MOFs and evaluate their antibacterial activity. The results indicate that the modification of alginate-gelatin hydrogels with MOFs has been successfully synthesized, as evidenced by FTIR, XRD, and SEM-EDS analyses. The materials successfully produced include Hy/Zn-BDC, Hy/Zn-Fer, and Hy/Zr-BDC. Antibacterial activity testing shows that adding MOF into the hydrogel matrix significantly increases the inhibition against S. aureus and E. coli compared to the hydrogel without MOF. Among the three MOF variants, Hy/Zn-BDC showed the highest antibacterial activity, followed by Hy/Zn-Fer and Hy/Zr-BDC. Specifically, Hy/Zn-BDC inhibited S. aureus growth by 95% and E. coli by 100%, accompanied by the lowest effective inhibitory concentration values (2.0 mg/mL and 2.4 mg/mL, respectively). These results demonstrate the high effectiveness of Zn-based MOF in enhancing the antibacterial performance of the hydrogel as well as its potential development for wound dressing applications.